Meningeal Mast Cells Contribute to ATP-Induced Nociceptive Firing in Trigeminal Nerve Terminals: Direct and Indirect Purinergic Mechanisms Triggering Migraine Pain - Koroleva, Ksenia; Gafurov, Oleg; Guselnikova, Valeriia; Nurkhametova, Dilyara; Giniatullina, Raisa; Sitdikova, Guzel; Mattila, Olli S.; Lindsberg, Perttu J.; Malm, Tarja Maarit; Giniatullin, Rashid (Frontiers in Cellular Neuroscience, 2019)
Peripheral mechanisms of primary headaches such as migraine remain unclear. Meningeal afferents surrounded by multiple mast cells have been suggested as a major source of migraine pain. Extracellular ATP, released during migraine attacks is a likely candidate for activating meningeal afferents via neuronal P2X receptors. Recently, we showed that ATP also increased degranulation of resident meningeal mast cells (Nurkhametova et al., 2019). However, the contribution of ATP-induced mast cell degranulation in aggravating the migraine pain remains unknown. Here we explored the contribution of meningeal mast cells in the pro-nociceptive effects of extracellular ATP. The impact of mast cells on ATP mediated activation of peripheral branches of trigeminal nerves was measured electrophysiologically in the dura mater of adult wild type (WT) or mast cell deficient mice. We found that spontaneous spiking activity in meningeal afferents, at baseline level, was not different in two groups. However, in WT mice, meningeal application of ATP dramatically (24.6-fold) increased nociceptive firing peaking at frequencies around 10 Hz. In contrast, in mast cell deficient animals, ATP-induced excitation was significantly weaker (3.5-fold). Application of serotonin to meninges in WT induced strong spiking, analogous to ATP. Moreover, in WT mice, the 5-HT3 antagonist MDL-7222 inhibited the ATP induced nociceptive firing. Our data suggest that extracellular ATP activates nociceptive firing in meningeal trigeminal afferents via amplified degranulation of resident mast cells in addition to direct excitatory action on the nerve terminals. This highlights the importance of mast cell degranulation via extracellular ATP in aggravating the migraine pain.